The Effect of Play Puzzle on Social Adapted Ability in Mental Retardation Students in SDLB Dharma Wanita Bengkulu - Dian Dwiana; Buyung Keraman; Emilita Julika Sari (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Mental retardation is a condition in which the child so that the child can not experience barriers through optimal development. Mental retardation is a global problem with major implications particularly for developing countries. Number of children with special needs in Indonesia is about 7% of the total number of children aged 0-18 years or a total of 6.23 million. In children with mental retardation learning process more focused on activities to train children with skills to enable them to function in an environment sosial. This study to determine the effect of Puzzle Play Against Social Adaptability on Mental Retardation Students in SDLB Dharma Women in Bengkulu. This research method using a research design Pre Exsperimental Design with draft form one group pretest-posttest, way of taking a sample is taken using total sampling with a sample of 12 respondents. used in this study are primary data, the data acquired, processed and analyzed using univariate and bivariate analysis using T. Test The results showed that the average number of children who have mental retardation prior to the puzzle game has a social adaptation unfavorable and the average number of children who have mental retardation after doing a puzzle game has a social adaptation good enough and no effect between playing puzzle to adaptability social in students with mental retardation in SDLB Dharma Women in Bengkulu City 2017 (p = 0.004). Suggested to the health public expected to make efforts to improve the health of children with mental retardation by performing group therapies in children with mental retardation regularly by medical personnel trained in the art so that the social problems of children with mental retardation can be minimized. Keywords: mental retardation, puzzle games, social adaptation